Comparison of glutaminase and cancer antigen 125 for distinguishing benign and malignant ovarian tumors - Gatot Nyarumenteng Adhipurnawan Winarno; Jusuf Sulaeman Effendi; Ali Budi Harsono; Siti Salima; Bagja Dumas Darwizar; R. M. Sonny Sasotya; Anita Rachmawati; Ayu Insafi Mulyantari; Nurvita Trianasari; Budi Handono (Wiley, 2023)
Abstract Increasing demand for glutaminase (GLS) due to high rates of glutamine metabolism is considered one of the hallmarks of malignancy. In parallel, cancer antigen 125 (CA‐125) is a commonly used ovarian tumor marker. This study aimed to compare the roles of GLS and CA‐125 in distinguishing between benign and malignant ovarian tumors. The research was conducted as a comparative study, enrolling 156 patients with ovarian tumors. Preoperative serum CA‐125 and GLS levels were analyzed to evaluate their effectiveness in distinguishing between benign and malignant ovarian tumors. The results revealed that the mean levels of CA‐125 and GLS were significantly higher in malignant ovarian tumors compared with benign ones (389.54 ± 494.320 vs. 193.15 ± 529.932 (U/mL) and 17.37 ± 12.156 vs. 7.48 ± 4.095 (μg/mL), respectively). The CA‐125 and GLS cutoff points of 108.2 U/mL and 18.32 μg/mL, respectively, were associated with malignant ovarian tumors. Multivariate analyses showed that GLS had higher predictive capabilities compared with CA‐125 (odds ratio 9.4 vs. 2.1). The accuracy of using GLS combined with CA‐125 was higher than using CA‐125 alone (73.1% vs. 68.8%). In conclusion, higher levels of CA‐125 and GLS are associated with malignant ovarian tumors. GLS outperforms CA‐125 in distinguishing between benign and malignant ovarian tumors. The combination of GLS and CA‐125 demonstrated improved accuracy for distinguishing benign and malignant ovarian tumors when compared with using CA‐125 alone.